Public Manager Leadership Model Compatible with Millennials - Chairunisa, Frida; Tonapa, Jessica Fransisca (KnE Social Sciences, 2022)
Millennials are increasingly more prominent in government bureaucracy. Recent public service recruitment has led to an increase of 24% in the number of Generation Y employees in the public service force. These new generations are exposed to a bureaucratic culture that is peculiar to their own character which favors flexibility in terms of working time and venue, as well as being technologically savvy. On the contrary, public service leaders are generally from Generation X and have a leadership style which is at odds with the millennial work culture, resulting in a generation gap. This study, therefore, attempted to explore a leadership model which is compatible with millennials. The study employed a qualitative descriptive approach. Data were collected using participant observation and interviews with informants representing millennials. The study proposed four aspects that millennials require from a leader. First, millennials prefer their superiors as coaches who support them in finding solutions to their problems rather than as managers. Second, millennials prefer collaborating in carrying out their tasks. Third, they expect their superiors to be fair and objective in assessing their performance. Lastly, millennials need their supervisors to motivate them. Keywords: leadership model, millennial generation, digitalization and automation